Study of the spatial and temporal distributions of tidal flat surface sediment based on multitemporal remote sensing - Zhang, Nan; Li, Huan; Zhang, Jiabao; Chen, Jiayin; Wu, Hongbo; Gong, Zheng (Frontiers in Marine Science, 2023)
The ecological environment of tidal flats often changes due to tidal erosion and sedimentation. The distribution of tidal flat surface sediment is a natural reflection of the changes in the external dynamic environment, and it is of great significance to study the spatial and temporal distribution patterns. In this study, four phases of Sentinel-2 multispectral images were collected and combined with field data from the Doulonggang tidal flat in Jiangsu Province, China. The output structure of the traditional convolutional neural network was improved to establish an inversion model for the sediment composition of the tidal flat, which was used to obtain the spatial distribution of the sediment. The inversion accuracy was higher than 80% compared with the measured results. The seasonal and interannual variation patterns of sediment components in the tidal flat of Doulonggang from 2017 to 2022 were analysed. The surface sediment particle size of the tidal flat in Jiangsu varied seasonally and was coarse in summer and fine in winter. Additionally, the sediment composition tended to coarsen, showing an interannual change trend of increasing sand content and decreasing clay and silt contents.